Integrating Character Education Management for Moral Development: A Qualitative Case Study at Darussalam Islamic Vocational School, Medan - Muhammad Ridho Alfatah; Amiruddin Siahaan; Fatkhur Rohman (Yayasan Sembilan Pemuda Indonesia, 2027)
Character education in vocational schools faces unique challenges due to the dual demands of academic competence and professional character formation. This study examines the implementation of character education management in fostering students’ moral development at an Islamic vocational school in Medan, Indonesia, focusing on planning, implementation, evaluation, and obstacle mitigation. Using a qualitative case study approach, data were collected through in-depth interviews with seven key informants (principal, vice principal, teachers, and students), observation, and document analysis. The findings reveal that character education management operates through integrated, systematic, and sustainable processes: planning is needs-based and participatory; implementation occurs through formal learning, school culture, religious habituation, and role modeling; evaluation employs multiple instruments including attitude assessments and parental collaboration. However, significant obstacles include insufficient parental supervision and the negative influence of social media. The school addresses these through reinforcing religious practices, personal development programs, and strengthening school-family partnerships. This study contributes to understanding how vocational schools can systematically manage character education to produce graduates with both professional competence and moral integrity. It recommends enhanced collaboration frameworks and digital literacy programs to address external environmental challenges.